Hawkes Learning Systems: Statistics. - Hilbe, Joseph M. (American Statistician, 2008)
The Hawkes Learning Systems: Statistics is an interactive multimedia courseware that offers competent and thorough instruction of the subject material. It is a method of instruction by which the student is presented with a 972-page text, video clips, a number of tutorials with audio, homework assignments, and practice problems. A CD-ROM, which necessitates only a single simple installation process, contains everything but the course text. The Internet is only required if homework and tests are to be assessed by the instructor at a distance. Overall, this courseware is one of the most impressive and useful on the market.